Mutilação cognitiva do clitóris: regimes de verdade sobre o corpo sexuado da fêmea humana - Jara, Iaci da Costa (2019)
The perception about the own body or about the body of others requires a specific vocabulary and a full range of categories to be understood and enunciated. From the first spark of thought to its enunciation, the apprehension of this organic mass that composes us depends on the culturally determined ways of seeing, naming, describing and classifying. Thus, it is proposed a sociological reading of biological knowledge in order to understand how the natural sciences found a knowable body called and identified as "female body". The objective of the present research is to understand the formation of clitoris knowledges focused on the regimes of truth about the human sexed body. Having as analytic support the genealogy of power of Michel Foucault, problematizations about the conditions of enunciability of bodies with clitoris are made. This investigation starts from technical knowledge of gynecology and psychoanalysis until arrive at the analysis of empirical objects present in brazilian daily life as a song, some jokes and a Science textbook that integrates educational public policies through the National Textbook Program. It is found that the formation of the western disciplines operated a clitoris cognitive ablation that is diffused by the daily relations sustaining power effects that restrict the possibilities of sexual and social fulfillment of the human females.